2021
DOI: 10.2147/ijn.s321612
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting of Endoplasmic Reticulum by Redox-Deubiquitination Regulation for Cancer Therapy

Abstract: Background Recently, nanocatalyst-induced endoplasmic reticulum (ER) stress for cancer therapy has been attracting considerable attention. However, cancer cells are often able to overcome ER stress-induced death by activating the unfolded protein response (UPR), making nanocatalytic monotherapy a poor defense against cancer progression. Purpose In this study, to improve the nanocatalytic treatment efficacy, a phase change material (PCM) was used to encapsulate the upstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Some previous studies have shown that the excessive ROS induced the damage of the cell membrane . In addition, the ER is vulnerable to ROS attack. , The western blot revealed that the expression of ER stress markers, including BiP (ER chaperones, a binding immunoglobulin protein) and phosphorylated-eIF2α (eukaryotic initiation factor 2α), was significantly increased in SKOV3 cells after the incubation with DOX or RGD-CaPO/DOX for 48 h. In addition, it should be noted that another ER stress marker, CHOP, a transcription factor closely associated with apoptosis, was obviously increased after incubation with DOX or RGD-CaPO/DOX, which suggested that ER stress induced by DOX could further promote cell apoptosis (Figure B). However, the ER stress could promote calcium disorders in tumor cells since ER was well recognized as the intracellular Ca 2+ store .…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies have shown that the excessive ROS induced the damage of the cell membrane . In addition, the ER is vulnerable to ROS attack. , The western blot revealed that the expression of ER stress markers, including BiP (ER chaperones, a binding immunoglobulin protein) and phosphorylated-eIF2α (eukaryotic initiation factor 2α), was significantly increased in SKOV3 cells after the incubation with DOX or RGD-CaPO/DOX for 48 h. In addition, it should be noted that another ER stress marker, CHOP, a transcription factor closely associated with apoptosis, was obviously increased after incubation with DOX or RGD-CaPO/DOX, which suggested that ER stress induced by DOX could further promote cell apoptosis (Figure B). However, the ER stress could promote calcium disorders in tumor cells since ER was well recognized as the intracellular Ca 2+ store .…”
Section: Resultsmentioning
confidence: 99%
“…Also, Biao Cai and his colleagues developed an efficient approach, by regulating redox homeostasis concurrently with the activity of deubiquitinases (DUBs), to convert the pro-survival unfolded protein response (UPR) into the pro-apoptotic one (Fig. 5 ) [ 113 ]. A nanocatalytic system, tLyP-1/PR-619/Fe 3 O 4 @PCM (tPF@PCM) co-loaded with Fe 3 O 4 nanoparticles and the pan-DUB inhibitor PR-619, was synthesized by taking advantage of a melting point-controlled thermal responsive phase-change material (PCM).…”
Section: Treatment Of Renal Cell Carcinoma Using Nanomedicinementioning
confidence: 99%
“…C Schematic of the treatment regimen for 786-O tumor-bearing mice. Figure adapted from Biao Cai et al [ 113 ] …”
Section: Treatment Of Renal Cell Carcinoma Using Nanomedicinementioning
confidence: 99%
“…These hydrophobic TRIDENT PCMs encapsulated with a broad-spectrum antibiotic (imipenem, IMP) and IR780 and subsequently coated with lecithin and DSPE-PEG 2000 not only resulted in the NIR-assisted melting of the nanotransporter but also damaged the membrane facilitating the permeation, as well as interfering in the cell wall biosynthesis and enable bacterial death (Figure 2C) (Qing et al, 2019). In this regard, several PCMs-based on LA and SA, as well as oleic acid, were fabricated for nanotheranostics with the ability of hyperthermia-triggered spatiotemporally tunable drug release (Cai et al, 2021;Lai et al, 2022).…”
Section: Phase-change Materials-based Platformsmentioning
confidence: 99%